Starter Feeding Supplementation Alters Colonic Mucosal Bacterial Communities and Modulates Mucosal Immune Homeostasis in Newborn Lambs - Liu, Junhua; Bian, Gaorui; Sun, Daming; Zhu, Weiyun; Mao, Shengyong (Frontiers in Microbiology, 2017)
This study aims to investigate the effect of starter feeding supplementation on colonic mucosal bacterial communities and on mucosal immune homeostasis in pre-weaned lambs. We selected eight pairs of ten-day-old lamb twins. One twin was fed breast milk (M, n = 8), while the other was fed breast milk plus starter (M+S, n = 8). The lambs were sacrificed at 56 days age. Colonic content was collected to determine the pH and the concentrations of volatile fatty acids (VFA) and lactate. The colonic mucosa was harvested to characterize the bacterial communities using Illumina MiSeq sequencing and to determine mRNA expression levels of cytokines and toll-like receptors (TLR) using quantitative real-time PCR. The results show that starter feeding decreased luminal pH and increased the concentrations of acetate, propionate, butyrate, total VFA, and lactate in the colon. The principal coordinate analysis and analysis of molecular variance show that starter feeding supplementation significantly affected the colonic mucosal bacterial communities with a higher relative abundance of the dominant taxa unclassified S24-7, Oscillibacter, Prevotella, Parabacteroides, Bifidobacterium, Ruminobacter, and Succinivibrio, and a lower proportion of unclassified Ruminococcaceae, RC9_gut_group, Blautia, Phocaeicola, Phascolarctobacterium, unclassified BS11_gut_group, unclassified family_XIII, and Campylobacter in lambs. Meanwhile, starter feeding decreased mRNA expression of TLR4 and cytokines TNF-α and IFN-γ in colonic tissue. Furthermore, the changes in the colonic mucosal mRNA expression of TLR and cytokines were associated with changes in mucosal bacterial composition. These findings may provide new insights into colonic mucosal bacteria and immune homeostasis in developing lambs.